WUJUD BELA NEGARA MELALUI KOMPONEN CADANGAN BERDASARKAN UU NO 23 TAHUN 2019 - Borhanndono Setiaji (2023)
The protection of the entire Indonesian nation and the entire Indonesian territory is the primary goal of the Preamble of the 1945 Constitution of the Republic of Indonesia. One of these is government policy, which creates a reserve component from various societal components. The Indonesian National Army, which is governed by Law No. 23 of 2019 about Management of National Resources for State Defense, is organized according to its nature as a component to reinforce, enlarge, and promote the primary component. The approach taken in this writing is normative legal research to determine whether the laws and regulations that apply to the reserve component (KOMCAD) and the form of state defense are consistent and appropriate. A conceptual approach is also used to collect primary data from direct field research on reserve component members who have been formed and superiors at the ministry of defense. The writing methodology uses qualitative descriptive writing skills, such as in-depth explanations and methodical problem-solving. The study's findings are contained in Article 28 paragraph (2) of Law No. 23 of 2019, which specifies that participation in the reserve component program is optional. According to members of the reserve component and superiors at the ministry of defense, the reserve component implements the form of state defense by attending basic military training (latsarmil) for three months.